Null-Zins-Politik und PPP: ein Kaleidoskop zu Fallbeispielen von Markt- und Staatsversagen - Ernst Mönnich (Vierteljahrshefte zur Wirtschaftsforschung, 2018)
Seit 2008 bedroht, ausgehend vom Finanzsektor, eine Wirtschaftskrise wie 1929 unser System. Nach kurzen koordinierten fiskalpolitischen Interventionen liegt seit Jahren die Stabilisierungslast allein bei den Zentralbanken. In der Eurozone hält die Null-Zins-Politik nun schon fünf Jahre an. Diese Situation bewirkt wiederum einen Lobbydruck des Finanzsektors für gleichzeitig risikoarme und renditestarke Anlagen zur Stabilisierung des tradierten Geschäftsmodells. Hierfür hat der Investitionsbedarf im Infrastrukturbereich zentrale Bedeutung. Um diesem Mangel Rechnung zu tragen, erscheinen Public Private Partnerships (PPP) eine Win-win-Lösung zu sein. Bevor man dieser Idee folgt, sollten allerdings Langfristerfahrungen zu PPP ausgewertet werden. In diesem Beitrag werden durch eine Aktualisierung von Fallstudien zu PPP im Wasser- und Abwasserbereich Ergebnisse zu den langfristigen finanzwirtschaftlichen Folgen dargestellt. Die Hypothese dieses Beitrages: Empirische Erfahrungen stehen im Gegensatz zur Erwartung einer Win-win-Lösung durch PPP. – – Induced by the financial sector in 2008, an economic crisis similar to that of 1929 is threatening our system. After a short period of cooperative fiscal policy, the task of stabilization now rests fully with the EZB. Zero Interest Rate Policies have marked the Euro zone for around five years. This in turn forces the finance sector to lobby for investments with low risks and high profits in order to stabilize traditional business models. The investment gap in infrastructure is hereby of central importance. Public Private Partnerships (PPP) seem to be the win-win solution to fill this gap. Before pursuing this idea, however, it might be wise to evaluate long term experience with PPP. This paper focusses on the long term financial results of PPP in the water and waste water sector. The analysis was made by actualization of broader case studies in this area. The hypothesis in this contribution: Empirical experience does not confirm the expectations of PPP as a win-win solution. The results in brief: Banks and operating agencies are the winners. Municipalities implementing infrastructural measures, along with their customers and fee payers, suffered losses. PPP led to an increase in shadow budgets and therefore these projects are quite the opposite of a sustainable fiscal policy. As such, the paper argues for regulation of PPP projects not only in the investigated area but also for the upcoming Federal Infrastructure Agency and the European Fund for Strategic Investments.
Keywords: H44; H54; L33; 330; Public private partnership; market and state failure